Optimalisasi Kemampuan Digital Calon Guru Matematika melalui Pelatihan Animasi Grafis Interaktif dengan Animaker - Faridhatun Nasikah; Ali Wardoyo; Muhammad Adi Priyanto; Surya Sari Faradiba (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2024)
The training on using Animaker was conducted to optimize the digital competence of prospective mathematics teachers at the Islamic University of Malang in creating interactive and contextual learning media. This activity aimed to enhance the skills of future teachers in utilizing technology to present abstract mathematical concepts visually and dynamically. The training methods included introduction, mentoring, and evaluation of the development of learning media using Animaker. The results showed a significant improvement in students' understanding and use of Animaker, with 100% of respondents recognizing it as an effective solution for learning in the digital era. This training underscores the importance of digital competence for prospective teachers in addressing the challenges of modern education. Recommendations for similar programs include continuous implementation with extended durations to accommodate more in-depth skill development.